Teacher’s Competence in Teaching 21st Century Literature: Basis for Faculty Development Program - Salaguinto, Roel Jhon (Studies in Technology and Education, 2024)
The primary objective of this study was to assess the proficiency of educators instructing Twenty-First Century Literature from the Philippines and the World in senior high schools within Legislative District 2, Division of Isabela, during the academic year 2019-2020. Employing a quantitative research approach, the study adopted a descriptive-comparative method to analyze data. Data collection techniques comprised administering a test on the subject's content covering first-quarter and second-quarter topics and a survey focusing on instructional methodologies and assessment practices. The quantitative analysis centered on delineating respondents' profiles and evaluating their competence levels, emphasizing comparing significant differences in competence levels concerning the content when categorized by selected profile variables. Profile variables were analyzed using frequency and percentages, while the test results involved computing correct responses and corresponding percentages to gauge teachers' competence levels accurately. By employing a quantitative framework, this research seeks to provide insights into the effectiveness of pedagogical practices in teaching Twenty-First Century Literature from the Philippines and the World. Using statistical analysis facilitates a systematic examination of educators' competencies, enabling stakeholders to identify areas for improvement and implement targeted interventions. Ultimately, this study contributes to enhancing the quality of education delivery and promoting better student outcomes within the context of literature instruction in the specified academic setting.